ASSOCIATION OF CARDIO METABOLIC AND ANTHROPOMETRIC RISK FACTORS AMONG IMPAIRED FASTING GLUCOSE SUBJECTS IN RURAL PONDICHERRY POPULATION. - R. SOBANA; K. JAIGANESH; R. RAMESH; S.VADIVEL; V. KUZHANDAI VELU; M. GANESH (International Journal of Pharma and Bio Sciences, 2014)
Screening for Impaired fasting glucose (IFG) in the early stage of Diabetes mellitus can avert the long term complications. Cross-sectional study was conducted in 500 study subjects in order to assess the IFG status and to find relationship between plasma triglyceride level (TAG) and anthropometric risk factors of rural Pondicherry population. Study groups were divided into two groups; above and below 40 years of age. Subjects with IFG in the study population was 21.3%. When compared to normo glycemic, there was a significant increase in Insulin resistance, TAG and HDL in IFG population in the study groups. In subjects with above 40 years of age, a significant difference was noted with WHR (p=0.03). Insulin resistance was assessed by HOMA IR, which had a significant association with WHR in subjects with above 40 years age (r=0.9; p=0.03) but not with BMI (r=0.4; p=0.57). In subjects with below 40 years of age, HOMA IR showed a significant correlation with BMI (r=0.8; p=0.004) and WHR (r=0.7; p=0.5). TAG and HDL significantly associated with BMI in both groups. HOMA-IR can be of additional value in screening IFG in both above and below 40 years of age.